2022
DOI: 10.1038/s41467-021-27882-5
|View full text |Cite
|
Sign up to set email alerts
|

NuA4 and H2A.Z control environmental responses and autotrophic growth in Arabidopsis

Abstract: Nucleosomal acetyltransferase of H4 (NuA4) is an essential transcriptional coactivator in eukaryotes, but remains poorly characterized in plants. Here, we describe Arabidopsis homologs of the NuA4 scaffold proteins Enhancer of Polycomb-Like 1 (AtEPL1) and Esa1-Associated Factor 1 (AtEAF1). Loss of AtEAF1 results in inhibition of growth and chloroplast development. These effects are stronger in the Atepl1 mutant and are further enhanced by loss of Golden2-Like (GLK) transcription factors, suggesting that NuA4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 106 publications
0
31
0
Order By: Relevance
“…For example, MtINGs also bind H3K4me2 in vitro and H3K4me2 was recently shown to correlate with reduced transcript levels in rice (Oryza sativa), indicating that it functions as a repressive epigenetic mark (Liu et al, 2019). Furthermore, mass spectrometry and other assays have shown that AtING2 forms a complex with the Arabidopsis acetyl transferase transcriptional co-activator NuA4 (Bieluszewski et al, 2015;Bieluszewski et al, 2022;Espinosa-Cores et al, 2020), consistent with the ING domain of the yeast ING (YNG2) forming part of the structural complex of yeast NuA4 (Xu et al, 2016). Thus, MtING2 protein interactors should be identified in planta to further analyze how MtING2 regulates gene expression and chromatin modifications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MtINGs also bind H3K4me2 in vitro and H3K4me2 was recently shown to correlate with reduced transcript levels in rice (Oryza sativa), indicating that it functions as a repressive epigenetic mark (Liu et al, 2019). Furthermore, mass spectrometry and other assays have shown that AtING2 forms a complex with the Arabidopsis acetyl transferase transcriptional co-activator NuA4 (Bieluszewski et al, 2015;Bieluszewski et al, 2022;Espinosa-Cores et al, 2020), consistent with the ING domain of the yeast ING (YNG2) forming part of the structural complex of yeast NuA4 (Xu et al, 2016). Thus, MtING2 protein interactors should be identified in planta to further analyze how MtING2 regulates gene expression and chromatin modifications.…”
Section: Discussionmentioning
confidence: 99%
“…During the preparation of this study, Zhou et al (2022) found that the Arabidopsis eaf6 mutant shows growth inhibition and leaf yellowing and that the NuA4 complex is involved in transcriptional activation, specifically in light-responsive genes. Another research group reported that the loss of Arabidopsis Esa1-associated factor 1 (EAF1) inhibited growth and chloroplast development ( Bieluszewski et al, 2022 ). These findings are consistent with our phenotypic observations, such as growth inhibition with reduced chlorophyll content during the vegetative phase in the double homozygote hwe1/2 .…”
Section: Discussionmentioning
confidence: 99%
“…The strategy used for introducing mutations to target genes was previously described by Bieluszewski et al, (2022); two target sequences spaced 200 – 400 bp apart were selected to generate polymorphisms that could potentially be identified by PCR. Guide RNAs (gRNAs) were designed using the CRISPOR tool, to evaluate the potential likelihood of generating double strand breaks while predicting possible off-target binding sites in the genome (Concordet and Haeussler, 2018).…”
Section: Methodsmentioning
confidence: 99%